PENGARUH ETIKA KERJA ISLAM TERHADAP SIKAP AKUNTAN DALAM PERUBAHAN ORGANISASI DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Astri Fitria (EKUITAS (Jurnal Ekonomi dan Keuangan), 2003)
The objective of the study is to analyze the impact of Islamic work ethic toward accountant attitude lo changing organization with commitment organization as a variable intervening. Population for this research is all of intern accountants, education accountants and accountant staf working Islam-organization basic in Indonesia. Data were collected via questionnaires. A total of 295 accountants were responded to this research. Data were analyzed by using Structural Equation Model (SEM).The result of the analysis support four hypotheses proposed in this research, there are; Islamic work ethic positive impact affective commitment, continuance commitment and normative commitment; Islamic work ethic positive impact cognitive, affective and behavioral tendency from attitude toward changing organization; affective commitment positive impact cognitive, affective and behavioral tendency from attitude toward changing organization; there is a negative impact between continuance commitment to cognitive, affective and behavioral tendency from attitude toward changing organization; normative commitment positive impact cognitive, affective and behavioral tendency from attitude toward changing organization; affective commitment mediated  Islamic work ethic to cognitive, affective and behavioral tendency from attitude toward changing organization; continuance commitment mediated Islamic work ethic to cognitive, affective and behavioral tendency from attitude toward changing organization; normative commitment mediated Islamic work ethic to cognitive, affective and behavioral tendency from attitude toward changing organization.